An analysis of customer satisfaction on employee professionalism: a comparison between Islamic and conventional banks in Malaysia. Issue 9 (20th July 2020) - Kamarudin, Ainatul Aqilah; Kassim, Salina
Abstract : Purpose: This paper aims to make a comparative analysis about the level of customer satisfaction on employee professionalism between Islamic and conventional banks in Malaysia. It also explores the important factors that attract customers to banks and identifies the strategies to improve customer satisfaction on employee professionalism. Design/methodology/approach: This study uses a quantitative approach, where questionnaires are distributed to a total of 312 respondents. Findings: The results show that customers are more satisfied with the conventional banks' employees in terms of their reliability, responsiveness, assurance and empathy, except for tangibility, where they are more satisfied with the Islamic banks' employees. It is also found that customers who have been engaging with the bank for more than one year consider each dimension of employee professionalism as important in ensuring their satisfaction with the bank. Research limitations/implications: This study is conducted in Malaysia and the respondents of this study are limited to 312 respondents only. Originality/value: This study provides some insights on the area of service quality and customer satisfaction from a developing country's environment (Malaysia) using the modified SERVQUAL model to perceive professionalism. This paper also explores a more specific area by highlighting the significance of service quality towards customer satisfaction from the perspective of gender, religion and respondents' period of being a customer to the bank.